A Study on Ceramsite Production Using Dredging Sea Mud and Its Biofilm Formation Capacity Evaluation. (6th December 2018) - Xia, Ting; Li, Yue; Xiao, Zhixing; Wang, Shixiang; Wu, Qingkai; Sun, Suwen; Peng, Hui; Chen, Dan; Wang, Zhihua
Abstract : Dredging sea mud produced during the coastal infrastructure construction has been gradually becoming an environmental problem in China. Making ceramsite is an attractive way to convert the waste sea mud to resources used for many industrial sectors. However, the imapct of preheating and sintering conditions on the ceramsite properties and the biofilm formation capacity of the ceramsite are still poorly understood. This study aims to fill these knowledge gaps. Results suggested the optimal conditions for the preheating temperature was 350° C, the preheating time was 15 min, the sintering temperature was 1040° C, and the sintering time was 9 min. The dredging sea mud-derived ceramsite showed better biofilm formation capacity with high COD and NH4 + -N removal performance compared with the commercial ceramsites. The content of the chloride ion in the ceramist granules is close to zero, and the low cost of this material, implying this dredging sea mud-derived ceramsite, could be an engineering favorable material for using it as a biocarrier in the real application.